Do Fully Threaded Transiliac–Transsacral Screws Improve Mechanical Stability of Vertically Unstable Pelvic Fractures? A Cadaveric Biomechanical Analysis. Issue 1 (January 2021) - Shannon, Steven F.; Oppizzi, Giovanni; Schloss, Michael G.; Atchison, Jared; Nascone, Jason; Sciadini, Marcus; Zhang, Li-Qun; O'Toole, Robert V.; Jaeblon, Todd
Abstract : Objective: To determine whether fully threaded transiliac–transsacral (TI-TS) fixation is biomechanically superior to partially threaded TI-TS fixation of vertically unstable transforaminal sacral fractures. Methods: Vertically unstable zone 2 sacral fractures were created in 20 human cadaveric pelves with a unilateral osteotomy and resection of 1 cm of bone through the foramen of the sacrum to represent comminution. Ten specimens received either 2 7.3-mm fully threaded or 2 7.3-mm partially threaded TI-TS screw fixation at the S1 and S2 body, and every specimen received standard 3.5-mm 8-hole parasymphyseal plating anteriorly. Each pelvis was loaded to 250 N at 3 Hz for 100, 000 cycles and then loaded to failure. The primary outcome was fracture displacement at the S1 foramen, which was measured at 25, 000, 50, 000, 75, 000, and 100, 000 cycles. Secondary outcomes were simulated clinical failure of ≥1 cm displacement at the S1 foramen to determine occurrence probability of failure, and load at failure was defined as 2.5 cm of the linear loading system displacement. Specimens in the fully threaded and partially threaded cohorts were otherwise respectively comparable in regards to age, gender, and bone density. Results: Five of the 10 TI-TS partially threaded specimens experienced simulated clinical failure with >1 cm displacement at the S1 foramen compared with 0 of the 10 TI-TS fully threaded cohort (50% vs. 0%, P = 0.03). The mean maximal displacement at the S1 foramen was greater in the partially threaded cohort (9.3 mm) compared with the fully threaded cohort (3.6 mm; P = 0.004). Fully threaded specimens also demonstrated greater mean force to failure than the partially threaded specimens (461 N vs. 288 N; P = 0.0001). Conclusions: Fully threaded TI-TS screw fixation seems to be mechanically superior to partially threaded fixation in a cadaveric vertically unstable transforaminal sacral fracture model with significantly less displacement of the posterior pelvic ring and greater load to failure.